Time to the Peak, Shape of the Curve and Combination of These Glucose Response Characteristics During Oral Glucose Tolerance Test as Indicators of Early Beta-cell Dysfunction in Obese Adolescents - Lavinia La Grasta Sabolić; Marija Požgaj Šepec; Maja Cigrovski Berković; Gordana Stipančić (Galenos Yayincilik, 2021)
Objective:Characteristics of the glucose response during oral glucose tolerance test (OGTT) may reflect differences in insulin secretion and action. The aim was to examine whether timing of the glucose peak, shape of the glucose curve and their combination could be indicators of beta-cell dysfunction in obese/severely obese adolescents with normal glucose tolerance (NGT).Methods:Data from 246 obese/severely obese adolescents who completed OGTT were reviewed. Out of 184 adolescents with NGT, 174 could be further classified into groups based on timing of the glucose peak (early/30 minutes vs late/≥60 minutes) and shape of the glucose curve (monophasic vs biphasic). Groups were compared with respect to insulin sensitivity (whole body insulin sensitivity index - WBISI), early-phase insulin secretion (insulinogenic index - IGI) and beta-cell function relative to insulin sensitivity (oral disposition index - oDI).Results:Late glucose peak (p=0.004) and monophasic glucose curve (p=0.001) were both associated with lower oDI after adjustment for age, sex, puberty stage and body mass index z-score. Among obese/severely obese adolescents with NGT, those with coexistent late glucose peak and monophasic glucose curve had lower oDI than those with early glucose peak and biphasic glucose curve (p=0.002). Moreover, a combination of late glucose peak and monophasic glucose curve was the most powerful predictor of the lowest oDI quartile [odds ratio (OR): 11.68, 95% confidence interval: 3.048-44.755, p<0.001].Conclusion:Late timing of the glucose peak, monophasic shape of the glucose curve and, in particular, a combination of those characteristics during OGTT may indicate early beta-cell dysfunction in obese/severely obese adolescents with NGT.